Organization and Performance of Cotton Sectors in Africa : Learning from Reform Experience - Tschirley, David; Poulton, Colin; Labaste, Patrick (World Bank, 2012)
Cotton is a major source of foreign exchange earnings in more than 15 countries across all regions of Sub-Saharan African (SSA) and a crucial source of cash income for millions of rural people in these countries. The crop is, therefore, critical in the fight against rural poverty. The World Bank and other development institutions have been and are currently assisting many cotton exporting countries of SSA to improve their cotton sector performance through projects supporting investment as well as through policy and institutional reform. Many SSA countries have been implementing or are considering implementing reforms of their cotton industries. The ultimate objective of the reform programs is to strengthen the competitiveness of cotton production, processing, and exports in an increasingly demanding world market and to ensure long-term, sustainable, and equitable growth for these major sectors of many African economies. The reform programs generally entail redefining the role of the state; facilitating greater involvement of the private sector and farmer organizations; ensuring greater competition in input and output markets; improving productivity through research and development, extension, and technology dissemination; and seeking value addition through market development and processing of cotton lint and by-products. A number of SSA cotton sectors, especially in West and Central Africa (WCA), are currently facing serious short-term financial difficulties. It is important to clarify that the purpose of this report is not to provide quick solutions to these short-run problems. Rather, it is to step back, build up a reliable broad assessment of cotton sector performance from detailed empirical information, and thereby provide guidance for the design of strategies that will address the long-term challenges of cotton production and marketing in Africa. Finally, to ensure that a broad perspective was brought to bear, the study was entrusted to a team which includes independent researchers and experts in the field of cotton.